A Case Study on an Engineered Timber Building in Johor Bahru - Tan, Bo Yu; Yeoh, Eng Chuan (Recent Trends in Civil Engineering and Built Environment, 2022)
Engineered timbers are nowadays widely used as construction materials and might be a kind of high demand materials in common construction of buildings of structures in the future generation. In fact, the engineered timber has gained popularity to our community as the pros outweighs the cons. The objectives in this study are to study the advantages of engineered timber building with five real cases around the world and to investigate the material quantity comparison of an engineered timber building in Malaysia as well as to produce a 3D model simulation with construction sequence of an engineered timber building in Malaysia. This study will mainly focus on the three major materials such as Laminated veneer lumber (LVL), Glue-laminated timber (Glulam) and Cross-laminated timber (CLT) with their benefits of their suitability to be used in construction of a building. Comparison of material quantity can also be determined in this study by analysis of result of a specified engineered timber building with other conventional buildings using steel. Application of 3D model such as SketchUp Pro software with Building Information Model (BIM) tool is used to produce a 3D model simulation of an engineered timber building in Malaysia. A simple 3D design of model will be produced at the end of this study and the material quantity in term of volume and mass will then be compared by using specified method.